DINAMICHE CO-EVOLUTIVE DI PROSSIMITÀ - Valentina Evangelista (Bollettino della Società Geografica Italiana)
Proximity is a central tenet of a large and inter-disciplinary field of research (geographical studies, management and economic studies, organizational studies). The aim of the paper is observe the co-evolution of proximities in an healthcare case study by analysing the dynamic relations and the co-evolution between the different dimensions of proximity – geographical, organizational, institutional, social, cultural, cognitive and technological – and the Abruzzo inter-hospitals system’s relations. Data were analysed by a Multiple Quadratic Assignment Procedure (MQAP). The results show that the different dimensions of proximity affect the hospital system, but each in a different manner and with a role that changes over time. Theoretical background, methodological and conceptual limitations, and future directions of research are discussed.